Improving Population Administration Services at the Buleleng Regency Population and Civil Registry Office through the Development of 6 Service Innovations, Detailed Service Information Systems, and Service Monitoring Displays - Hermawan, Dadang; Suniantara, I Ketut Putu; Pratami, Ni Wayan Cahya Ayu; Nirmala, Bagus Putu Wahyu; Darsana, I Made (Journal of Ecohumanism, 2025)
The Population and Civil Registration Service of Buleleng Regency has been managing population data since 2022 through the AKUOnline application and in 2023 it will develop into AKUOnline-NG. In 2024, AKUOnline-NG will be available in a PWA (progressive web apps) version and can be accessed via mobile devices by all residents of Buleleng Regency. With the largest population in Bali Province, public administration services for population through AKUOnline-NG need to be improved. In order to prepare open access for AKUOnline-NG to 826,000 residents of Buleleng and anticipate complaints/questions related to AKUOnline-NG which currently only provides a login page. In addition, to accommodate 6 innovation services (BALITA, AKSAMA, NYAKSI, SAKKINAH, APISAN and KK DILAN) which currently do not have features, AKUOnline-NG needs to be further developed. The purpose of this study is the development of AKUOnline-NG in accommodating 6 innovation services, improving the detailed service information system (SIM) not just a login page, and developing a service monitoring display so that evaluations can be carried out on public services. In addition, this study also aims to determine the impact of the implementation of 6 digital-based service innovations, detailed SIM services and monitoring displays on improving public services. During the implementation of the study, qualitative research was conducted to determine the business processes that would be digitized and the agile development approach so that it could involve users, especially Disdukcapil. In addition, quantitative research was conducted with the USE questionnaire (usefulness, satisfaction and ease of use) as a model of technology acceptance.